1990
DOI: 10.7326/0003-4819-112-12-921
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection in Patients with Nonalcoholic Chronic Liver Disease

Abstract: Our results indicate that HCV infection probably plays an important etiologic role in cryptogenic liver disease and, in some patients, in chronic hepatitis B. Determining whether anti-HCV are present appears to be useful for differentiating viral from autoimmune chronic liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 8 publications
2
27
0
1
Order By: Relevance
“…Therefore, our findings confirm the virus C as the most important agent of non-A, non-B hepatitis in hemodialysis patients [7,14,[18][19][20], and infection by this virus was related to a longer time on dial ysis and transfusions [14-16, 18, 19, 26], but there are other unidentified mechanisms of transmission of the virus apart from the parenteal administration of blood products [9,14,16], as 5 patients with anti-HCV antibody had never been transfused.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, our findings confirm the virus C as the most important agent of non-A, non-B hepatitis in hemodialysis patients [7,14,[18][19][20], and infection by this virus was related to a longer time on dial ysis and transfusions [14-16, 18, 19, 26], but there are other unidentified mechanisms of transmission of the virus apart from the parenteal administration of blood products [9,14,16], as 5 patients with anti-HCV antibody had never been transfused.…”
Section: Discussionsupporting
confidence: 54%
“…However the preval ence of anti-HCV Ab among patients with non-A, non-B hepatitis differs among studies [4][5][6][7], Such differences may be explained if viruses other than HCV cause non-A, non-B hepatitis. In addition, Ab determinations may yield false-negative results, especially if they are per formed too early or too late in the course of the infection [4], Finally, a group of investigators have reported a high incidence of false-positive results in patients with auto immune hepatitis, which they attributed to nonspecific binding of circulating IgG to the ELISA plates [8], More recently, another group of investigators have suggested that the presence of low-titer autoantibodies represents an epiphenomenon and does not invalidate the serologic diagnosis of HCV infection in patients with chronic hep atitis [7], The incidence of false-positive tests in other forms of liver disease is not well established [5,7].…”
mentioning
confidence: 95%
“…2 Most of those infected with HCV acquired the disease 10 to 20 years ago, before identification of the virus and the availability of screening tests. [3][4][5] The recognition of potential risk factors and the improved safety of the blood supply have led to a dramatic decrease in the incidence of new HCV infections in recent years. However, the overall prevalence of chronic infection has not fallen because most acutely infected patients develop chronic infection.…”
mentioning
confidence: 99%